2023
DOI: 10.1186/s12913-023-09217-w
|View full text |Cite
|
Sign up to set email alerts
|

Using telehealth to support community health workers in Uganda during COVID-19: a mixed-method study

Abstract: Background At the onset of the COVID-19 pandemic, a local consortium in Uganda set up a telehealth approach that aimed to educate 3,500 Community Health Workers (CHW) in rural areas about COVID-19, help them identify, refer and care for potential COVID-19 cases, and support them in continuing their regular community health work. The aim of this study was to assess the functioning of the telehealth approach that was set up to support CHWs during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…As Table 1 shows 18 Studies were undertaken in the Asia (India [ 36 – 43 ], China [ 30 , 44 47 ], Qatar [ 48 , 49 ], Bangladesh [ 50 ], Indonesia [ 51 ], Nepal [ 52 ]), 11 in the North America (United States [ 17 , 20 , 29 , 31 , 53 – 58 ], Dominican Republic [ 59 ]), 10 in the Europe (Austria [ 60 ], France [ 61 ], United Kingdom (UK) [ 62 , 63 ], Slovenia [ 64 ], German [ 65 ], Ireland [ 66 ], Poland [ 16 ], Serbia [ 67 ], Spain [ 68 ]), 3 in Africa (Tunisia [ 69 ], Egypt [ 70 ], Uganda [ 71 ]), and 1 in South America (Bolivia [ 22 ]). Among them, 11 studies were published in 2020, 11 in 2021, 9 in 2022, and 12 in 2023, and a summary of them is presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As Table 1 shows 18 Studies were undertaken in the Asia (India [ 36 – 43 ], China [ 30 , 44 47 ], Qatar [ 48 , 49 ], Bangladesh [ 50 ], Indonesia [ 51 ], Nepal [ 52 ]), 11 in the North America (United States [ 17 , 20 , 29 , 31 , 53 – 58 ], Dominican Republic [ 59 ]), 10 in the Europe (Austria [ 60 ], France [ 61 ], United Kingdom (UK) [ 62 , 63 ], Slovenia [ 64 ], German [ 65 ], Ireland [ 66 ], Poland [ 16 ], Serbia [ 67 ], Spain [ 68 ]), 3 in Africa (Tunisia [ 69 ], Egypt [ 70 ], Uganda [ 71 ]), and 1 in South America (Bolivia [ 22 ]). Among them, 11 studies were published in 2020, 11 in 2021, 9 in 2022, and 12 in 2023, and a summary of them is presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The concerns of the callers should be characterized into five groups including exacerbation of preexisting mental and physical illness (30.9%), known case of mental or physical illness (19%), Covid-19 related mental health concerns (22.2%), administrative or logistic issues (7.1%), newonset mental health‑related concerns or illnesses (15.9%). 38 Kok et al, 2023 [ 71 ] Uganda Assessing the functioning of the telehealth approach that was set up to support community health workers during the Covid-19 pandemic Mixed-method Toll-free line/ Community health workers March 2020/ seven days a week, from 7:00 to 23:00 from Monday to Friday, and from 9:00 to 18:00 on Saturday and Sunday Educating Community Health Workers in rural areas about Covid-19, refering and caring for potential Covid-19 cases, and supporting them in continuing their regular community health work Covid-19 queries, Psychological issues The telehealth approach did prove useful for supporting community health workers regular health services in rural communities. The community health workers felt better informed, less isolated and indicated that the support helped them to provide better care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations